Bio-aerogels derived from corn stalk and Premna Microphylla leaves as eco-friendly sorbents for oily water treatment: The role of microstructure in adsorption performance. (1st June 2023) - Ye, Rongchuan; Li, Huosheng; Long, Jianyou; Wang, Yaxuan; Peng, Dan
Abstract: Internal microstructure significantly affects the physicochemical properties and the adsorption ability of bio-aerogels. The effect of microstructure structure of bio-aerogels on oil sorption is still remain unexplored, thus needs a systematic and comparative study. In this study, cellulose nanofibers (CNF) derived from corn stalk were blended with Premna Microphylla leaves (PML) to fabricate bio-aerogels with distinct internal microstructure via two freeze casting methods, unidirectional and random freezing, aiming to shed lights on the correlation between capillary structure and oil sorption mechanism. At an optimized CNF/PML mass ratio of 9, the silanized CNF/PML bio-aerogels synthesized via random (SC9/P1R) and unidirectional freeze-drying (SC9/P1U) exhibited unorderly porous structure and parallel capillary structure, respectively. The blending of pectin-rich PML with CNF at an appropriate amount enhanced the crosslinking and reduced the bulk density and pore wall density of bio-aerogels, thereby enhancing the oil adsorption ability. Unorder-microstructure bio-aerogels were superior to order-microstructure ones in terms of oil sorption performance. The maximum machine oil sorption capacity for SC9/P1R and SC9/P1U was 130.1 and 97.5 g/g, respectively. Efficient separation of the oil and organic solvents from the organic-water mixture was achieved by SC9/P1R because of its high hydrophobicity and olephilicity. Besides, SC9/P1R can be reused for at least 15 cycles, showing prominent recovery potential. Unlike most other research, this works provides a proof of the superiority of random microstructure bio-aerogels over the finely-tuned capillary-structured ones for selective oil sorption. Therefore, under some circumstances, the isotropic bio-aerogels may be more effective than the anisotropic ones in applications to oil pollution treatment. Graphical abstract: Image 1 Highlights: Bio-aerogel is prepared with green pectin (PML) and corn stalk nanofiber (CNF). CNF/PML hybrid aerogels show high porosity, low density, and good elasticity. Random freeze-drying is superior to unidirectional freeze-drying for oil sorption. CNF/PML hybrid aerogels show oil sorption capacity of 82–161 g/g.